Phoma medicaginis stimulates the induction of the octadecanoid and phenylpropanoid pathways in Medicago truncatula - Kamphuis, L.; Williams, A.; Kuster, H.; Trengove, R.; Singh, K.; Oliver, R.; Ellwood, Simon (Wiley-Blackwell Publishing Ltd., 2012)
Gene expression changes and metabolite abundances were measured during the interaction of Medicago truncatula with the fungal necrotrophic pathogen Phoma medicaginis in leaf tissue of susceptible and resistant accessions. Over 330 genes were differentially expressed in plants infected with P. medicaginis relative to mock-inoculated plants at 12 h post-inoculation. Of these, 191 were induced in either the resistant or the susceptible accession, with 143 genes repressed. Expression changes were observed in genes involved in the oxidative burst, cell wall strengthening and lipid metabolism, as well as several transcription factors. Genes related to salicylic acid, jasmonate and ethylene responses were up-regulated, as well as genes leading to the production of jasmonic acid. Significant induction of genes in the phenylpropanoid pathway leading to lignin and isoflavonoid biosynthesis occurred. High-pressure liquid chromatography with UV detection (HPLC-UV) identified several phenolic compounds induced by P. medicaginis, as well as constitutively higher levels of phenolic compounds, in the resistant M. truncatula accession. Differentially regulated genes induced in both the resistant and susceptible accessions, but with different kinetics, and constitutively more highly expressed and induced phenolic compounds provide candidates for functional analysis. Taken together, these results highlight the importance of the octadecanoid and phenylpropanoid pathways in defence against this necrotrophic pathogen.